Impact of removable denture prosthesis on chewing efficiency - جركس منار (Latakia University Journal -Medical Sciences Series, 2023)
This study aimed to assess the masticatory efficiency in patients with a removable dental prosthesis. The study was conducted on a convenient sample of patients aged 50 and above, with removable prostheses in at least one jaw. Patients were asked to chew samples of digestive biscuits, apple, and carrot, until the sensation of swallowing. The recorded masticatory function parameters were: chewing time, the number of mastication cycles, and mean masticatory cycle duration. We found out that the masticatory functional parameters registered statistically significant differences according to the chewed food, most likely this being in relation to food’s consistency, wetting, and adherence. High positive correlations were found between the chewing time and the number of mastication cycles for all three foods taken into consideration. Higher values for chewing time and number of mastication cycles were found for all foods in patients with complete dentures. The residual teeth number and the type of prosthetic rehabilitation favor the adaptation and improvement of masticatory parameters and can have marker value for masticatory efficiency.